PENGARUH MOTIVASI TERHADAP KINERJA PEGAWAI DI KANTOR KELURAHAN KAWATUNA - Atnila, Atnila (Katalogis, 2017)
This study aimed to determine the influence of motivation on employee performance at Kawatuna Subdistrict Office. This study used quantitative research method which was done through data collecting in the field, so this study was designed to use explanatory survey technique. This study used multiple linear regression analysis technique with saturated sampling technique. Respondents in this study amounted to 32 respondents. The results showed that the partial influence of motivation on employee performance at Kawatuna Subdistrict Office was 0.720, meaning it was in influencing cathegory. The simultaneous influence of motivation on employee performance at Kawatuna Subdistrict Office was 0.720 or 72%, while the rest 28% was owned by other variables that were not studied. The calculation process resulted that F-count = 32.229 at real level Î± = 0.05 or sig < 0.05, with significance value = 0.000. Therefore, it can be stated that the independent variables simultaneously had significant influence on the dependent variables. Based on the results, the hypothesis stating that motivation extrinsically and intrinsically had significant influence on employee performance at Kawatuna Subdistrict Office was received.